Copyright Protection for Wood Mask Artists: a Regulatory Analysis - Pujiyono Pujiyono; Slamet Subiyantoro; Sufmi Dasco Ahmad; Kristiani Kristiani; Dwi Maryono (Yustisia Jurnal Hukum, 2021)
Wood Masks are works of art inherited from ancestors that are still produced in Indonesia. But in its development, apart from facing quality challenges, another challenge is the protection of its creators. The easy plagiarism of works is the reason the competition for works becomes unhealthy. A legal breakthrough is needed so that the creator of the work gets moral and economic protection. This research was conducted normatively with a statutory and conceptual approach, the data collected was secondary data. The results of the study indicate that there is a weakness in the substance of the offense which is the complaint offense, in addition to low public literacy, the registration of works in the government is low.